2021
DOI: 10.1002/anie.202112150
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Optical Visualization of Proton Transport Pathways at Water–Solid Interfaces

Abstract: Probing proton transport is of vital importance for understanding cellular transport, surface catalysis and fuel cells.Conventional proton transport measurements rely on the use of electrochemical conductivity and do not allow for the direct visualization of proton transport pathways. The development of novel experimental techniques to spatiotemporally resolve proton transport is in high demand. Here,b uilding upon the general conversion of aqueous proton flux into spatially resolved fluorescence signals,w eo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Many researchers have studied the effects of material structure and composition on proton transport in ceramics. Investigating the surface chemistry between solid and ambient gas interface can lead to better understanding of the ion site activity and proton and oxygen transport. Encouraging results have established that in different environment, proton transport properties are strongly influenced by hydration-induced changes in surface chemistry. Stub et al showed that different structures of the adsorbed water layer on oxide surface affect the activation energy for proton transport. To study the mechanism of surface hydration at relevant conditions, such as temperature and atmosphere, in situ spectroscopic probes are highly effective approaches. In particular, in situ X-ray photoelectron spectroscopy (XPS) has provided inspiring results on proton conductors: our previous work showed the V O •• filling upon hydration is associated with charge redistribution between ions; Jarry et al , observed that surface composition affects OH – formation under different conditions for BaCe x Zr 0.9‑x Y 0.1 O 2.95 thin films.…”
mentioning
confidence: 99%
“…Many researchers have studied the effects of material structure and composition on proton transport in ceramics. Investigating the surface chemistry between solid and ambient gas interface can lead to better understanding of the ion site activity and proton and oxygen transport. Encouraging results have established that in different environment, proton transport properties are strongly influenced by hydration-induced changes in surface chemistry. Stub et al showed that different structures of the adsorbed water layer on oxide surface affect the activation energy for proton transport. To study the mechanism of surface hydration at relevant conditions, such as temperature and atmosphere, in situ spectroscopic probes are highly effective approaches. In particular, in situ X-ray photoelectron spectroscopy (XPS) has provided inspiring results on proton conductors: our previous work showed the V O •• filling upon hydration is associated with charge redistribution between ions; Jarry et al , observed that surface composition affects OH – formation under different conditions for BaCe x Zr 0.9‑x Y 0.1 O 2.95 thin films.…”
mentioning
confidence: 99%